Gender-Based Violence in Three Poems The Monster He’s Become by Patricia A Flaming (2021), Returning Faith by Lynette Gutwein (2011), and They Don’t Know by Brian E Pardee (2020) - Faizza, Nur; Al-Hafizh, Muhd (English Language and Literature, 2024)
This research is an analysis of three poems entitled The Monster He’s Become by Patricia A Flaming (2021), Returning Faith by Lynette Gutwein (2011), and They Don’t Know by Brian E Pardee (2020). This analysis explains the form and impact of the treatment of violence experienced by women in the three poems. This study also shows how victims of violence resist the acts of violence they receive. The study of these poems is analyzed with feminist theory which focuses on gender-based violence. The results of this study show that victims experience three types of violence, in the form of physical violence, verbal violence and sexual violence. This study shows that there are impacts such as fear, self-doubt, physical injury, distrust to partner and distrust to other people like family and neighbors. Then in this study shows that there is resistance by women such as staying away from the violence zone and staying alive.